Challenges in the face of profession nursing’s teacher - the past, present, future - Marć, Małgorzata; Binkowska-Bury, Monika; Penar-Zadarko, Beata (Nursing Problems / Problemy Pielęgniarstwa, 2008)
The roots of nursery are very closely connected with a care of the sick. The system of nursing education and part professional nursing teacher. Has changed a lot since time. The aim of the study is to present challenges in the face of profession nursing’s teacher in variable model of nurse educating. The subject of analysis are legal regulations to standards of practical training, in particular the ones concerning the teaching body. It implies the necessity of change of teacher’s function - he should support and inspire in process of solving problems.